Peran UMKM Ramah Lingkungan Dalam Peningkatan Ekonomi Lokal (Godhong Asri Dalam Industri Eco-Printing) - Putri, Firyal Khaznah; Anggraini, Lathifah Bunga; Dyatmiko, Oktavia Ramadhani; S, Saridawati (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This analysis discusses the significant role of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia's economy. Although not as large as major corporations, MSMEs have the potential to introduce local products to the global market. This study examines the contribution of MSMEs in supporting the national economy, focusing on the Godhong Asri business, which explores the factors contributing to its success in eco-printing, as well as the challenges and opportunities it faces amid industry competition. Established in March 2021, Godhong Asri employs eco-printing—a technique that uses plants to create patterns on fabric or leather. This business not only contributes to the economic improvement of local communities but also embeds sustainability values within the creative industry.